KEJADIAN NEUROPATI DAN VASKULOPATI PADA PASIEN ULKUS DIABETIK DI POLIKLINIK KAKI DIABETIK - Christia, Srisabrina; Yuwono, Agus; Fakhrurrazy, Fakhrurrazy (Jurnal Berkala Kedokteran, 2015)
Diabetic ulcer is a diabetes mellitus (DM) complication, where its growth is affected by many factors such as neuropathy and vasculopathy. The aim of this study was to identify the incidence number of neuropathy and vasculopathy on diabetic ulcer patients at RSUD Ulin Banjarmasin and RSUD Dr. H. M. Ansari Saleh Banjarmasin from June to August 2014. This is an observational descriptive study with cross sectional approach. A total of 100 diabetic ulcer patient samples were chosen using purposive sampling method. Neuropathy was assessed using Michigan neuropathy screening instrument (MNSI) and vasculopathy was assessed using Ankle Brachial Index (ABI). The results showed that from 100 samples, 100 (100%) persons were neuropathic, while 31 (31%) of them were vasculopathic hence they suffered from both neuropathy and vasculopathy, a condition commonly known as neuroischemia.Â Keywords: diabetic ulcer, neuropathy, vasculopathy